VOLCANIC PIPES AS CLUES TO UPPER MANTLE PETROGENESIS: MESOZOIC AR-AR DATING OF THE MINUSINSK BASALTS, SOUTH SIBERIA - Malkovets V.G.; Taylor L.A.; Litasov Yu.D.; Litasov K.D.; Travin A.V. (My University, 2003)
Ar/Ar dating of alkali basalt pipes and dikes of the North Minusinsk basin has provided an important chronologic framework for Altay-Sayan fold belt and Central Asia region. These Mesozoic basalt pipes have become the subject of special interest due to the abundant occurrence of garnet-spinel and spinel lherzolite xenoliths. These rocks reveal information about the composition, structure, and thermal state of the Mesozoic upper mantle beneath the southwestern margin of the Siberian craton. Our detailed Ar/Ar dating has shown that the pipes and their related NW-trending dikes formed coevally, during a Late Cretaceous, short-time, magmatic impulse. Twelve plateau ages on feldspar megacryst and whole rocks between 72 ±2.7 and 79 ±2 Ma have been determined. Abundant E-W-trending dikes, previously though to be related to the Meso-Cenozoic subvolcanic complex, have a less alkaline composition, compared to the basanite pipes, with Early Permian Ar/Ar ages. The trachyte NW-trending dikes yielded an Early Permian, whole-rock plateau age of 262 ±2.5 Ma. The trachybasalts of the North Minusinsk basin have a Ar/Ar age of 392 ±11 Ma, i.e., Devonian.
Keywords: Mesozoic; Mesozoic; Мезозой